Knowledge, Attitude and Acceptance towards Coronavirus Disease 2019 (COVID-19) Vaccines among Healthcare Students of a Tertiary Care Teaching Hospital in South India: A Cross-sectional Study - Prabath, Indumathi; Ayyar, Porkodi; Navabalan, Vivekraj; Krishnan, Radhika (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Coronavirus disease 2019 (COVID-19) has imposed a serious health impact afflicting millions of people and halting global progress significantly. Albeit vaccines for COVID-19 emerged as a potent approach to overcome the morbidity, its suspicion had been persisting across diverse categories of people, including healthcare students. Since studies exploring the acceptance of vaccines among healthcare students from India were limited, this study has been formulated to evaluate the knowledge, attitude and acceptance of COVID-19 vaccines among healthcare students of a tertiary care hospital. Materials and Methods: This was a self-reporting questionnaire-based cross-sectional study conducted via online platforms. By convenience sampling method, participants were enrolled. Primary outcomes were expressed as frequency and Chi-square test was used for comparison between groups. Results: Out of 562 participants, there were 268 medical, 90 dental, 70 nursing and 134 allied health science students. Female participants (65.1%) were more compared to male participants (35.9%) and the mean age of participants was 19 years. Medical students had significantly better knowledge about vaccine doses (98.5%), route of administration (85.4%) and priority candidates for vaccines (95.9%) than students of other courses. Overall, 438 (77.9%) students were interested to receive COVID-19 vaccines. Fear of adverse effects (44.7%) was the major concern for vaccine administration among study participants. Medical course [Odds Ratio (OR) 3.95; 95% Confidence Interval (CI) 2.22-7.06] and family history of COVID-19 disease (OR 2.57; 95% C:1.28-5.17) positively influenced the willingness of students for vaccines. Conclusion: Maximum participants were convinced of COVID-19 vaccination and medical students exhibited better vaccine knowledge. This knowledge gap among healthcare students in diverse courses should be addressed via consistent vaccine sensitization programs.
Keywords: COVID-19; Vaccines; Knowledge; Attitude; Healthcare students